2015
DOI: 10.5455/aim.2015.23.369-373
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of SEPAS National Project Based on Electronic Health Record System (EHRS) Coordinates in Iran

Abstract: Background:Electronic Health Records (EHRs) are secure private lifetime records that can be shared by using interoperability standards between different organizations and units. These records are created by the productive system that is called EHR system. Implementing EHR systems has a number of advantages such as facilitating access to medical records, supporting patient care, and improving the quality of care and health care decisions. The project of electronic health record system in Iran, which is the goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The findings of the usability evaluations of Agharezaee [ 6 ], Abedi and Khajouei [ 16 ], Thyvalikakath [ 17 ] and Verheul [ 18 ] on other HISs as well as electronic health records also showed numerous usability problems in the principle of “consistency and standards”. As well, findings of Sadoghi [ 19 ], Meydani [ 20 ] and Asadi [ 21 ] illustrated that the standards are not adopted in HISs, while access to standard data in an organised format to provide appropriate and on-time healthcare service is highly significant [ 22 ]. It seems that the HISs have the same usability problems.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the usability evaluations of Agharezaee [ 6 ], Abedi and Khajouei [ 16 ], Thyvalikakath [ 17 ] and Verheul [ 18 ] on other HISs as well as electronic health records also showed numerous usability problems in the principle of “consistency and standards”. As well, findings of Sadoghi [ 19 ], Meydani [ 20 ] and Asadi [ 21 ] illustrated that the standards are not adopted in HISs, while access to standard data in an organised format to provide appropriate and on-time healthcare service is highly significant [ 22 ]. It seems that the HISs have the same usability problems.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study by Asadi et al, [32] revealed that information systems in Iran are mainly focused on financial objectives. Our findings revealed that mean system use among users of the nursing management department and psychiatric departments is generally low.…”
Section: Discussionmentioning
confidence: 99%
“…Development and use of messaging standards for EHRs are needed for information exchange (1)(2)(3)(4), and the absence of standards and lack of coordination between systems have made healthcare data sharing difficult (5)(6)(7)(8). Lack of standards also hinders the widespread use of EHRs and integrated systems in healthcare services in the Islamic Republic of Iran.…”
Section: Introductionmentioning
confidence: 99%